Restrictive mitral annuloplasty with or without surgical ventricular reconstruction in ischaemic cardiomyopathy: impacts on neurohormonal activation, reverse left ventricular remodelling and survival. (9th December 2013) - Kainuma, Satoshi; Taniguchi, Kazuhiro; Toda, Koichi; Funatsu, Toshihiro; Miyagawa, Shigeru; Kondoh, Haruhiko; Masai, Takafumi; Otake, Shigeaki; Yoshikawa, Yasushi; Nishi, Hiroyuki; Sakaguchi, Taichi; Ueno, Takayoshi; et al.
<x xml:space="preserve">Abstract</x> Aims In the STICH trial, adding surgical ventricular reconstruction (SVR) to coronary artery bypass grafting (CABG) reduced LV end‐systolic volume index (LVESVI) by 19%, as compared with 6% with CABG alone, providing no survival or functional benefits. Herein, we compared the efficacy of restrictive mitral annuloplasty (RMA) alone with that of RMA combined with SVR in patients with functional mitral regurgitation (MR). Methods and results One hundred and six patients with ischaemic cardiomyopathy underwent RMA with (n = 52) or without SVR (n = 54) for functional MR. Pre‐ and post‐operative (1 month) left ventriculography and longitudinal measurements of plasma BNP were performed. Pre‐operatively, patients who underwent RMA plus SVR had a larger LVESVI (126 ± 26 vs. 100 ± 24 mL/m2, P < 0.0001). After surgery, RMA plus SVR reduced LVESVI more than RMA alone (43% vs. 22%, P <0.0001), yielding a nearly identical post‐operative LVESVI (71 ± 17 vs. 78 ± 26 mL/m2). Survival rate was not different between the groups (4‐year survival, 62% vs. 62%, P = 0.99), though among patients with pre‐operative LVESVI ranging from 105 to 150 mL/m2, that was higher in the RMA plus SVR group (73% vs. 40%, P = 0.046), accompanied by a larger percentage reduction in plasma BNP from baseline to the latest follow‐up examination (63 ± 34% vs. 34 ± 46%, P = 0.012). After propensity score adjustment, patients with LVESVI ranging from 105 to 150 mL/m2 who underwent RMA alone showed a greater association with mortality (hazard ratio 7.5, 95% confidence interval 2.1–27, P = 0.010), as compared with those with LVESVI <105 mL/m2 who underwent RMA alone. Conclusions RMA plus SVR reduced LVESVI to a greater degree than RMA alone, neutralizing anticipated worse prognosis. Selected patients with functional MR and advanced LV remodelling may benefit by adding SVR to RMA.